2023
DOI: 10.1021/acschembio.3c00065
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Harmine-Mediated Inhibition of Human DNA Methyltransferases and Prostate Cancer Cell Growth

Abstract: Mammalian DNA methyltransferases (DNMTs), including DNMT1, DNMT3A, and DNMT3B, are key DNA methylation enzymes and play important roles in gene expression regulation. Dysregulation of DNMTs is linked to various diseases and carcinogenesis, and therefore except for the two approved anticancer azanucleoside drugs, various non-nucleoside DNMT inhibitors have been identified and reported. However, the underlying mechanisms for the inhibitory activity of these non-nucleoside inhibitors still remain largely unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…As de novo methyltransferases, DNMT3B are more biased towards methylating unmethylated CpG dinucleotides 26 . Studies have shown that when the adenine cavity of the SAM-binding pocket in DNMT3B is bound, its enzyme activity decreases, thus limiting the proliferation of prostate cancer 27 . The remaining DNA methyltransferases are generally thought to lack cytosine methyltransferase activity, although DNMT3L can increase the binding capacity of DNMT3B to the methyl donor S-adenosyl-L-methionine (SAM) to increase their activity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…As de novo methyltransferases, DNMT3B are more biased towards methylating unmethylated CpG dinucleotides 26 . Studies have shown that when the adenine cavity of the SAM-binding pocket in DNMT3B is bound, its enzyme activity decreases, thus limiting the proliferation of prostate cancer 27 . The remaining DNA methyltransferases are generally thought to lack cytosine methyltransferase activity, although DNMT3L can increase the binding capacity of DNMT3B to the methyl donor S-adenosyl-L-methionine (SAM) to increase their activity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…found that harmine inhibited prostate cancer cell growth by blocking mammalian DNMT activity. Harmine competitively binds to the SAM-binding site of the adenine domain in DNMT3B, thereby inhibiting the activity of the DNMT3B-3L complex and limiting prostate cancer cell proliferation ( 41 ). Therefore, harmine can serve as an important cell cycle regulator that inhibits tumor cell proliferation and exhibits antitumor activity.…”
Section: Mechanism Of Action Of Harmine In Cancermentioning
confidence: 99%